2019
DOI: 10.1136/thoraxjnl-2019-213233
|View full text |Cite
|
Sign up to set email alerts
|

Using digital technology for home monitoring, adherence and self-management in cystic fibrosis: a state-of-the-art review

Abstract: Digital healthcare is a rapidly growing healthcare sector. Its importance has been recognised at both national and international level, with the WHO recently publishing its first global strategy for digital health. The use of digital technology within cystic fibrosis (CF) has also increased. CF is a chronic, life-limiting condition, in which the treatment burden is high and treatment regimens are not static. Digital technologies present an opportunity to support the lives of people with CF. We included 59 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Home monitoring, trials involving physiotherapy and virtual clinics were also identified, although these have previously been used in trials in CF. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Home monitoring, trials involving physiotherapy and virtual clinics were also identified, although these have previously been used in trials in CF. 20 …”
Section: Discussionmentioning
confidence: 99%
“…8 Its use in CF has increased over the last 20 years yet there is currently limited evidence of its efficacy in improving long-term adherence in CF. 20 This study has highlighted that although technology is being used by a group within the CF community to aid treatment management; it is promoted more by HCPs than used in practice by the majority of pwCF at present. 21 In addition, the types of technologies preferred by pwCF can be different to what is recommended by their HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Home monitoring, trials involving physiotherapy and virtual clinics were also identified, although these have previously been used in trials in CF. 20 Ongoing studies including CFHealthHub 12 and Project Fizzyo 13 aim to address adherence in CF through the use of digital technology. Project Fizzyo combines the use of Fitbit exercise trackers with chipped airway clearance Open access devices with feedback given on technique via an App.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our iPad‐based group interventions were without the demands of travel or exposure to many of the common health infection risks that HPN patients encounter in clinic visits. Systematic reviews, meta‐analyses, and evaluations of Internet‐delivered interventions, including groups, have shown positive results in improving mental health of adolescents and young adults (Calthorpe et al, 2020; Nelson et al, 2006; Rogers et al, 2017). In one clinical trial using telehealth videophones, the young subjects' depression improved at a faster rate and parents reported fewer disruptive behaviors than families in outpatient group visits with controls matched on age and length of symptoms (Nelson & Duncan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Technical challenges with distance care have been written about previously (Calthorpe et al, 2020; Smith et al, 2015). These challenges include the occasional dropped or slow connections, pixel blurring, and the need for online security.…”
Section: Discussionmentioning
confidence: 99%